Використання неонових і голографічних ефектів у 3D-сценах Unreal Engine 5 - Кульбака, О. О. (ХНУРЕ, 2025)
This article focuses on the application of neon and holographic effects in 3D scenes created with Unreal Engine 5 (UE5), a leading tool for immersive visual design. It examines how UE5’s Lumen lighting system and emissive materials enable vibrant neon effects, while the Niagara particle system and shaders facilitate dynamic holographic visuals. The study highlights their role in enhancing futuristic aesthetics, such as cyberpunk environments, and their impact on user immersion. It also addresses performance optimization using Nanite and Lumen, ensuring quality across platforms. Ultimately, these effects enrich both the visual appeal and narrative depth of 3D scenes.
Keywords: голографічний ефект; Unreal Engine 5